An orientation program for nurses in a cardio thoracic intensive care unit - van der Bergh, D P; Nel, W E; Botes, A C (Curationis (Pretoria), 1997)
The objective of this qualitative, explorative and descriptive study was to explore and describe the contents and management of an orientation program for a specific cardio thoracic intensive care unit of a specific private hospital. The goals of the study were: Conducting a literature review to explore and describe the concepts identified in the conceptual framework and thereby lending theoretical support to the contents and management of the orientation program. To explore and describe the expectations of the learner with regard to the contents and management of the orientation program. To explore and describe the expectations of the senior professional nursing team with regard to the contents and management of the orientation program.